A Novel Scheduling Strategy for Crude Oil Blending - 摆亮 江永亨 黄德先 刘先广 (Chinese journal of chemical engineering, 2010)
For those refineries which have to deal with different types of crude oil, blending is an attractive solution to obtain a quality feedstock. In this paper, a novel scheduling strategy is proposed for a practical crude oil blending process. The objective is to keep the property of feedstock, mainly described by the true boiling point （TBP） data, consistent and suitable. Firstly, the mathematical model is established. Then, a heuristically initialized hybrid iterative （HIHI） algorithm based on a two-level optimization structure, in which tabu search （TS） and differential evolution （DE） are used for upper-level and lower-level optimization, respectively, is proposed to get the model solution. Finally, the effectiveness and efficiency of the scheduling strategy is validated via real data from a certain refinery.